2020
DOI: 10.21203/rs.3.rs-36706/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplement with whey protein hydrolysate in contrast to carbohydrate supports mitochondrial adaptations in trained runners

Abstract: Background: Protein supplementation has been suggested to augment endurance training adaptations by increasing mixed muscle and myofibrillar protein synthesis and lean body mass. However, a potential beneficial effect on mitochondrial adaptations is yet to be clarified.The aim of the present study was to investigate the effect of consuming whey protein hydrolysate before and whey protein hydrolysate plus carbohydrate (PRO-CHO) after each exercise session during a six-week training period compared to similarly … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Similarly, protein supplementation has been reported to improve performance and reduce markers of muscle damage during a strenuous one-week training camp in runners compared to an energy-matched carbohydrate supplement [ 8 ], as well as to promote adaptations ( e.g . increased lean mass, muscle oxidative capacity, and performance) in response to long-term endurance training [ 9 , 49 , 50 ]. It must be noted, however, that other authors found no beneficial effect of protein supplementation on performance or recovery indicators during a six-day training camp in professional cyclists [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, protein supplementation has been reported to improve performance and reduce markers of muscle damage during a strenuous one-week training camp in runners compared to an energy-matched carbohydrate supplement [ 8 ], as well as to promote adaptations ( e.g . increased lean mass, muscle oxidative capacity, and performance) in response to long-term endurance training [ 9 , 49 , 50 ]. It must be noted, however, that other authors found no beneficial effect of protein supplementation on performance or recovery indicators during a six-day training camp in professional cyclists [ 13 ].…”
Section: Discussionmentioning
confidence: 99%